IDENTIFIKASI TINGKAT PENCEMARAN PADA LAHAN PERTANIAN MENGGUNAKAN METODE KEMAGNETAN BATUAN - Azhari, Adinda Syifa; Agustine, Eleonora; Fitriani, Dini (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Every industrial activity has the potential to make pollution on agricultural land, in general waste out of that factory is dumped directly into the river, where the waste can be a waste of toxic for the environment. The study aims to get information from the soil sample has been meticulous about the level of pollution in farming caused by waste disposal a textile mill which is located in Bandung. The experiment at the different places, there is the area which located closer by pollution source (a) and area which far from pollution source (b). After weÃ¢â‚¬â„¢ve done the measurement, we got some data, there are PH (a) =7,8, PH(b) = 7,1,Ã‚ TDS dan EC (a) = 0,161 - 0,313 dan 0,34 - 0,627, TDS dan EC (b) = 0,06 - 0,206 dan 0,127 - 0,419, cfd % (a) = 0,66 Ã¢â‚¬â€œ 2,4 % , cfd % (b) = 3,26 Ã¢â‚¬â€œ 3,76 %. Ã‚ That data is shown the pollution of the soil at the place, it is area (a), which specification are PH (>>), TDS and EC (>>) and cfd % (<<), it means the soil is alkali with big grain and has high salt concentration. Keywords: Industrial textiles, pollution, land.